Compensation of Vestibular Function and Plasticity of Vestibular Nucleus after Unilateral Cochleostomy - Myung-Whan Suh; Jaihwan Hyun; Ah-Ra Lyu; Dong Woon Kim; Sung Jae Park; Jin Woong Choi; Gang Min Hur; Yong-Ho Park (Neural Plasticity)
Dizziness and vertigo frequently occur after cochlear implantation (CI) surgery, particularly during the early stages. It could recover over time but some of the patients suffered from delayed or sustained vestibular symptoms after CI. This study used rat animal models to investigate the effect of unilateral cochleostomy on the vestibular organs over time. Twenty-seven Sprague Dawley rats underwent cochleostomy to evaluate the postoperative changes in hearing threshold, gain and symmetry of the vestibular ocular response, overall balance function, number of hair cells in the crista, and the c-Fos activity in the brainstem vestibular nucleus. Loss of vestibular function was observed during the early stages, but function recovered partially over time. Histopathological findings demonstrated a mild decrease in vestibular hair cells numbers. Increased c-Fos immunoreactivity in the vestibular nucleus, observed in the early stages after cochleostomy, decreased over time. Cochleostomy is a risk factor for peripheral vestibular organ damage that can cause functional impairment in the peripheral vestibular organs. Altered vestibular nucleus activity may be associated with vestibular compensation and plasticity after unilateral cochleostomy.